2019
DOI: 10.1162/jocn_a_01357
|View full text |Cite
|
Sign up to set email alerts
|

Visual Simultaneity Judgments Activate a Bilateral Frontoparietal Timing System

Abstract: In everyday life, we often make judgments regarding the sequence of events, for example, deciding whether a baseball runner's foot hit the plate before or after the ball hit the glove. Numerous studies have examined the functional correlates of temporal processing using variations of the temporal order judgment and simultaneity judgment (SJ) tasks. To perform temporal order judgment tasks, observers must bind temporal information with identity and/or spatial information relevant to the task itself. SJs, on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…As described thus far, the present fMRI study indicates that the right IPL is a neural correlate of tactile SJ. A similar right parietal area was also detected in audio-visual SJ 11 and visual SJ 37 . On the other hand, these studies also found SJ-specific activity in the right IFG and anterior insula, and the left cerebellum for audio-visual SJ 11 and in the bilateral IFG and the left TPJ for visual SJ 37 .…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…As described thus far, the present fMRI study indicates that the right IPL is a neural correlate of tactile SJ. A similar right parietal area was also detected in audio-visual SJ 11 and visual SJ 37 . On the other hand, these studies also found SJ-specific activity in the right IFG and anterior insula, and the left cerebellum for audio-visual SJ 11 and in the bilateral IFG and the left TPJ for visual SJ 37 .…”
Section: Discussionsupporting
confidence: 58%
“…A similar right parietal area was also detected in audio-visual SJ 11 and visual SJ 37 . On the other hand, these studies also found SJ-specific activity in the right IFG and anterior insula, and the left cerebellum for audio-visual SJ 11 and in the bilateral IFG and the left TPJ for visual SJ 37 . The neural activity of audio-visual SJ was detected using a colour judgement with attending to sounds for a control task, and that of visual SJ was detected using visual-orientation and colour judgements for control tasks.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations